PENGARUH PENDEKATAN INQUIRY TERBIMBING TERHADAP HASIL BELAJAR IPA SISWA KELAS VIII SMP N 3 KASIHAN BANTUL TAHUN AJARAN 2016/2017 - Nanang Haryanto; Sigit Sujatmika (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2017)
The aim of this study was to identify the descriptive trends of natural science learning outcomes of eighth-grade students SMP N 3 Kasihan Bantul academic year 2016/2017 which guided by inquiry learning approach and expository. Comparatively to determine the differences in natural science learning outcomes of eighth-grade students of SMP N 3 Kasihan Bantul academic year 2016/2017 between learning by using guided inquiry approach and expository. The research used Quasi-Experimental research type. Descriptively the results of the research showed that the trends of natural science learning outcomes eighth-grade students of SMP N 3 Kasihan Bantul academic year 2016/2017 which guided inquiry learning approach including very high category, while the use of expository learning models including in the high category. Comparatively, there were significant differences in natural science learning outcomes of eighth-grade students of SMP N 3 Kasihan Bantul academic year 2016/2017 between guided inquiry learning approach and expository. It Meant the were any influences of guided inquiry approach to natural science learning outcomes eighth-grade students of SMP N 3 Kasihan Bantul academic year 2016/2017.